On calculation electronic states of carbon nanotubes - Korostil, A.; Korostil, Yu. (Моделювання та інформаційні технології, 2010)
A new approach is development for description of physical properties of carbon nanotubes h taking into account their real atomic structure have been proposed. On the basis of the classical polynomial theory we have investigated main quantum of studding system. On the basis a functional integral representation for a statistic sum we have proposed an effective method for building of the closed self-consisted equations for Green functions of investigating system. The proposed approach is applicable for calculation of physical properties both single- and multiwall carbon nanotubes.